Barokní „světová kronika“ Andrease Augustina Fiedlera jako málo známý kulturněhistorický pramen - Jiří Wolf (Acta Universitatis Carolinae: Historia Universitatis Carolinae Pragensis)
In this contribution, the seldom investigated manuscript by a Chomutov burgess Andreas Augustin Fiedler († 1690) is placed in the context of Central European historiography. Subsequently, I outline the spatiotemporal coordinates of his chronicle and examine some of patchy and inconsistent information regarding places and times in the manuscript. In this connection, there emerge the following questions: Which events in the world’s history did Fielder find especially interesting? What areas were surveyed by spiritual vision of the small-town chronicler? How did Fiedler view the space of the night sky full of premonitions, praesagia? How did the Fiedler’s imagination handle the phenomena that were, in his view, harbingers of future events, such as comets and other celestial signs or ‘monstrous’ children?